Potencial alelopático de extratos de sementes de Physalis peruviana L. (Solanaceae) - Mariquito, Anderson (2016)
Physalis peruvianahas attracted the interest of Brazilian farmers due to the high market value of the fruits. However, the insertion of this exotic plant was not followed by studies on its allelopathic potential. Thus, due to relevant ecological and economic issues, the objective of this research was to verify the allelopathic potential of this plant determining the chemical classes present in the extracts. Extracts of hexane, ethyl acetate and methanol of Physalis peruvianaseeds at concentrations of 0 , 200, 400 and 800mg/ L of lettuce (Lactuca sativa L.), and guinea grass (Panicum maximumJacq cv. Tanzania) were analyzed evaluating the following aspects: germination percentage, germination speed index (GSI), radicle length, shoot length, mitotic index, as well as preliminary phytochemical screening. The design was completely randomized with five repetitions. The results were submitted to the analysis of variance and the means were analyzed by the Scott Knott test at the level of 5% probability. Only the methanolic extractat the concentrations 400mg / L and 800mg / L affected the germination of lettuce while the other extracts and concentrations tested, significantly reduced the germination of (guinea grass) Panicum maximum. The ethyl acetate extract in all concentrations,was able to inhibit the germination of (guinea grass) Panicum maximum, but not the germination of lettuce. The GSI was reduced in both plants only in the extracts of ethyl acetate and hexane. The methanol extract, the only one in which there are coumarinsand saponins, had a significant effect on the mitotic index. These results indicate significant allelopathic effect of Physalis seed extracts on (guinea grass)Panicum maximum, which may represent a promising future use in sustainable agriculture